PEMANFAATAN SURAT KABAR SEBAGAI MEDIA KOMUNIKASI PUBLIK PEMERINTAH KOTA BUKITTINGGI (STUDI PADA DINAS KOMUNIKASI DAN INFORMATIKA KOTA BUKITTINGGI) - Afdal Rizky; Elva Ronaning Roem; Ernita Arif (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
The existence of newspapers as the main medium of public communication media in the midst of the development of information technology, became the interest of researchers to conduct qualitative descriptive research on the use of newspapers as a medium of public communication carried out by the Department of Communication and Information at the Bukittinggi Government. Data collection was done by interview, observation and documentation. The use of newspapers is analyzed using the Media Richness Theory, and the implementation of public communication activities using the Organization Public Relations Models approach. The results of this study indicate that local newspapers have been used as the main media in the implementation of public communication by the Bukittinggi Government, through a mutually beneficial professional cooperation agreement between the two parties. Local newspapers that have collaborated are used as a medium for disseminating information and disseminating messages by Diskominfo to the public. As a medium that favors text as the main element of delivering information and the use of appropriate and easy words can increase readers, so newspapers are very suitable for disseminating routine government policies, programs and activities. Newspapers should be avoided for spreading conflict or tragedy information, because there will be a lot of emotional information that will be filtered out.